Gambaran Tingkat Kebisingan Akibat Suara Kendaraan Bermotor di Beberapa Sekolah Berlokasi di Sekitar Jalan Raya kota Padang - Galan Eko Saputro; Meifal Rusli (Department of Mechanical Engineering, Universitas Andalas, 2019)
Concern about noise pollution has been increasing in worldwide nowadays, especially in industrial and urban areas. Children could be particularly vulnerable to the effects of noise because of its potential to interfere with learning at a critical development stage. Most of the learning occurs at school and thus noise exposure at school gives significant influence on learning performance. According to World Health Organization (WHO), traffic is one of the main sources of environmental noise exposure in urban communities, including school. This paper will review the noise level in some schools located near the main traffic road around Andalas and Simpang Haru area of Padang City, West Sumatera Province. Sound levels are measured at four points, i.e. at the main road in front of school, school gate, the nearest and farthest class room from the main road. The measurements are conducted from 7.00 am in the morning to 04.00 pm in the afternoon. It is found that almost in all positions in the schools are exposure by noise above the threshold limit value reversed by WHO and Indonesian Government 55 dBA. In the morning when the peak time of the traffic session, the noise levels from the class to the gate are around 70 dBA to 85 dBA, and its decrease to 50 dBA and 75 dBA in the afternoon. Some noise is possibly generated not only by traffic noise, but the noise graphics are seemed to be related to the traffic noise in the road.